2002
DOI: 10.1006/jfbi.2002.1879
|View full text |Cite
|
Sign up to set email alerts
|

The role of F-series prostaglandins as reproductive priming pheromones in the brown trout

Abstract: Electrophysiological studies demonstrated that the olfactory epithelium of mature male brown trout Salmo trutta parr was acutely sensitive to F-series prostaglandins (PGFs) PGF 1 and PGF 2 , with detection threshold concentrations of 10 11 . The olfactory epithelium was also sensitive to the PGF metabolite 15-ketoPGF 2 (threshold 10 8 ), but did not detect a further metabolite, 13,14,-dihydro-15-ketoPGF 2 . Immature brown trout did not detect any of the prostaglandins tested. Exposure of mature male brown tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…The PGF response threshold values in the present study are similar to those found in Atlantic salmon and Arctic charr (Moore & Waring, 1996; Sveinsson & Hara, 2000). The response threshold for PGF 2α in brown trout is also consistent with another EOG study (Moore et al ., 2002). Values of PGF detection thresholds of 10 −11 M for two catostomid species (Cardwell et al ., 1992), 10 −10 M and 10 −11 M, for common carp Cyprinus carpio L. and goldfish are also reported (Sorensen et al ., 1988; Irvine & Sorensen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The PGF response threshold values in the present study are similar to those found in Atlantic salmon and Arctic charr (Moore & Waring, 1996; Sveinsson & Hara, 2000). The response threshold for PGF 2α in brown trout is also consistent with another EOG study (Moore et al ., 2002). Values of PGF detection thresholds of 10 −11 M for two catostomid species (Cardwell et al ., 1992), 10 −10 M and 10 −11 M, for common carp Cyprinus carpio L. and goldfish are also reported (Sorensen et al ., 1988; Irvine & Sorensen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after collection, blood samples were centrifuged and plasma was decanted and frozen. Plasma was later analysed for content of 11KT and 17,20β‐P by specific radioimmunoassay (RIA) as described previously (Moore et al , 2002).…”
Section: Methodsmentioning
confidence: 99%
“…PGF 2α (Sigma) was dissolved and diluted in ethanol before priming. It has been previously shown that S. trutta males exposed to PGF 2α increases their volumes of milt and sex steroid hormone levels (Moore et al , 2002). The copper‐exposed group (five fish in each tank) was exposed to 10 or 100 µg l −1 copper for 4 days before being exposed to the priming solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations